METHOD OF TECHNICAL DIAGNOSING OF THE BORES OF FIREARMS BASED ON THE DETERMINATION OF THEIR GEOMETRIC CHARACTERISTICS - Kriukov, Oleksandr; Migura, Oleksii (Honor and Law, 2023)
The work is devoted to the justification of the method of technical diagnosing of the bores of firearms, which is based on determining their geometric characteristics using a laser triangulation measurement tool and creating a detailed image of the surface in a cylindrical coordinate system. An analysis of modern methods of technical diagnosing of the bores of firearms was carried out, and the contradiction between their capabilities and the growing needs of practice was determined. The need to create a diagnostic method and tool that would ensure obtaining a detailed image of the inner surface of the bore and identifying both the type of defect and the degree of its manifestation is substantiated. The detailed image of the inner surface of the bore should be presented in the form of a data array containing the spatial coordinates of the points on its inner surface and the corresponding values of the radius of the bore. It is shown that it is most expedient to diagnose the bore using the laser triangulation method, which makes it possible to determine their geometric characteristics and create tables of coordinates of surface points in a cylindrical coordinate system with a given step. The number of points at which measurements are made in each of the sections is chosen depending on the purpose of the research and the requirements for detailing the technical condition of the surface of the bore. The general principle of measurement based on the application of the triangulation method of determining distances to the controlled surface of the object, as well as the structure of the sensor and the features of its integration with the measuring probe and the positioning module, are considered. An approach to determining the required amount of measurement information and the number of control points is proposed. The method of grouping the measurement results into the given options for their presentation for the next analysis is defined.